Gambaran Pengetahuan Dan Sikap Ibu Dalam Mengobati Diare Menggunakan Tanaman Tradisional di Desa Milangasri Magetan - Samuel Budi Harsono; Irfan Zamzani; Liana Djeli Maesaroh (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In Indonesia, traditional medicine is still widely used by the community. Riskesdas data from 2010 to 2018, shows the use of traditional medicines has increased by 44.3%. The use of these traditional medicines to treat various diseases, one of which is diarrhea. Knowledge about the use of traditional medicinal plants to prevent and treat diarrhea has been passed down from generation to generation. The purpose of this study is to provide an overview of the knowledge and attitudes of mothers in treating diarrhea using traditional plants. This research is a non-experimental quantitative research with descriptive data presentation. Sampling was done by non random sampling technique using purposive sampling method. The research instrument used questionnaires and leaflets as educational media. Data analysis used the Kolmogorov-Smirnov test and the Wilcoxon test. The research sample was mothers aged 21-55 years who were in Milangasri Village, Magetan Regency. The results of the study obtained the number of samples of 95 respondents. The level of knowledge in the pre-test in the good category is 37.89% and the post-test in the good category is 91.58%, while the attitude level for the pre-test in the good category is 51.58% and the post-test in the good category is 89.47%. Kolmogorov test obtained results 0.000 < 0.05 which means the data is not normally distributed and Wilcoxon test results obtained 0.00 < 0.05 which indicates the influence of education on the level of knowledge and attitudes of respondents.